Respiratory resistance of the velopharynx after pharyngeal flap operation - Matsuya, Tokuzo; Nishio, Juntaro; Miyazaki, Tadashi; Wada, Takeshi; Fukuda, Tomiko; Inoue, Kazuo; Tanaka, Tsutomu; Hamamura, Yasuhi (Journal of Japanese Cleft Palate Association, 1980)
The present study was designed to clarify the aerodynamic changes after unified velopharyngeal plasty. Aerodynamic analysis made on 17 patients suggested the followings. (1) The nasal resistance tended to decrease gradually until 6 months after operation. (2) The nasal resistances of 12 adult subjects were quite different from those of 5 non-adult subjects. (3) No significant difference was noticed in the nasal resistance between inahalation and exhalation.